The seven wonders of the world - Spry-Leverton, Peter; Discovery Channel Video ([S.l.] : Discovery Channel Video [production company] ; Petaling Jaya : Wawasan Videovan [distributor], 1999)
Exploring the enduring fascination of the only surviving wonders, the pyramids. Ghosts of wonder demonstrates how the story of the wonders is also the story of the modern imagination
Bahan pembelian Kelab Pencinta Ilmu (KPI)
Title from title screen
Subtitles in Bahasa Indonesia
Written and presented by John Romer ; series producer, Nicholas Barton ; photography, Peter Greenhalgh, Micheal Miles ; film editor, Jonathan Cooke ; music, Barrington Pheloung
Keywords: Seven wonders of the world; Architecture, ancient; Curiosities and wonders